Relationships between satisfaction of Muslim Women on financial supports after divorce and ex husband compliance to the supports with post divorce welfare - Hasbullah@Abdullah, Muslihah; Mohd Zin, Najibah; Wok, Saodah (UPM Press, 2009)
The main objective of this study was to assess the welfare of divorced women in relation to financial supports after divorce, i.e. iddah maintenance, mut'ah, arrears of maintenance, and child maintenance. The specific objectives were to determine the divorced women satisfaction with the amount of financial supports, the ex-husbands' compliance to court-ordered financial supports, their satisfaction with post divorced welfare (levels of economic strain and depression), the relationship between satisfaction with the amount of financial supports and post-divorced welfare, as well as the relationship between ex husbands' compliance to court-ordered financial supports and post divorced welfare. Data were collected using a questionaire. The sample comprised of 201 divorced women selected from the cases recorded in the year 2003 till 2005 at the Shariah Subordinate Courts of Hulu Langat and Gombak Timur,Selangor. Pearson correlation showed two factors were negatively correlated with the economic welfare of the divorced women, i.e. the dissatisfaction with the amount of iddah maintenance, mut'ah and child maintenance. However on the contrary to the expectation, the divorced women's satisfaction with the amount of all types of financial supports provided by the ex husbands and their ex husbands' none or partial compliance to all types of financial supports was found to have no significant relationship with depression. The findings also indicated that the assessment of reasonable sum of financial supports and the effective enforcement of court order were significant factors that might augment the welfate of women after divorce.